2012
DOI: 10.1097/shk.0b013e3182690897
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic Shock Decreases Cerebral Blood Flow More Than What Would Be Expected From Severe Arterial Hypotension

Abstract: The effects of acute reduction in arterial blood pressure in severe anaphylactic shock (AS) on cerebral blood flow are of paramount importance to be investigated. We studied cerebral circulation and oxygenation in a model of severe AS and compared it with a pharmacologically induced arterial hypotension of similar magnitude. Anaphylactic shock was induced by 1 mg intravenous ovalbumin (OVA) in sensitized rats. Rats were randomized to three groups: (i) no resuscitation (OVA; n = 10) (ii) intravenous volume expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Doses reported were very different in those studies, from 2 IU IV to 40 IU plus infusion. In animal models, vasopressin has similar systemic effects than epinephrine but delays restoration of cerebral tissue oxygen pressure as compared to epinephrine [27,28]. The clinical consequences of these results are not known but underline the importance of taking into consideration regional circulations when assessing the efficacy of vasoconstrictors used in the resuscitation of AS.…”
Section: Vasopressinmentioning
confidence: 95%
See 1 more Smart Citation
“…Doses reported were very different in those studies, from 2 IU IV to 40 IU plus infusion. In animal models, vasopressin has similar systemic effects than epinephrine but delays restoration of cerebral tissue oxygen pressure as compared to epinephrine [27,28]. The clinical consequences of these results are not known but underline the importance of taking into consideration regional circulations when assessing the efficacy of vasoconstrictors used in the resuscitation of AS.…”
Section: Vasopressinmentioning
confidence: 95%
“…Whereas cerebral blood flow is conserved during pharmacologically-induced arterial hypotension, one study showed a linear relationship between cerebral cortical blood flow and blood pressure during hypotension in AS in a rat model [27]. AS resulted in severe impairment of cerebral blood flow and oxygenation, beyond what could be expected from the level of arterial hypotension.…”
Section: Altered Cerebral Blood Flowmentioning
confidence: 97%
“…The authors of this experiment definitely excluded peripheral vasodilatation as a cause of the registered anaphylactic cardiac damage [5]. Similarly, in a recent study [6], it was found that anaphylactic shock decreases cerebral blood flow more than what would be expected from severe arterial hypotension. This was attributed to direct action of anaphylactic mediators on the cerebral arterial system and not solely due to arterial hypotension.…”
mentioning
confidence: 87%
“…In the clinical setting,[31] there are current reports according to which patients with anaphylactic cardiac shock do not respond to fluid replacement but recover with current acute myocardial infarction protocol and antiallergic treatment thus denoting that the heart is primarily affected. Furthermore, other recent experiments[32] have shown that anaphylactic shock decreases cerebral blood flow more than what would be expected from severe arterial hypotension. This was attributed to the early and direct action of anaphylactic mediators on cerebral vessels.…”
Section: A Pathophysiologic Paradox: Ischemic Myocardial Damage Is Prmentioning
confidence: 99%